Distribution and Diversity of Echinoderms in the Coastal Waters of South Beach of Lombok Island - Syamsul Bahri; Lalu Raftha Patech; Zulhalifah Zulhalifah; Devi Ayu Septiani; Siswadi Siswadi (Jurnal Biologi Tropis, 2021)
Echinoderms are benthic animals that can be found in almost all marine ecosystems but are mostly found in the intertidal coastal zone. Echinoderms play an important role as deposit feeders. This study aims to look at the distribution patterns, diversity, and habitat conditions of species in the southern coastal waters of Lombok Island, namely Kute, Awang, and Gerupuk beaches. The field survey was conducted using the quadratic transect method and free collection in October - November 2020. Based on the results of the research, a total of 11 species of echinoderms were found in Lombok Island consisting of 4 classes. Diadema setosum and Tripneusteus gratila were the most common species, whereas Synapta maculate, Holothuria leucospilota, Echinotrix diadema, Holothuria atra, and Ophiocoma scolopendrina were found in small numbers with uniform distribution (Id <1). Diadema setosum distribution pattern has the highest abundance with a clustered distribution pattern (Id> 1) in Awang and Gerupuk, and Tripneusteus gratila in Kute and Awang. The Diversity Index value is different in each habitat. The highest Shannon-Wiener Diversity Index (HÃªÅ¾Å) was found in Gerupuk 2.18. The largest smoothing index is found at Awang 0.96. The largest Dominance Index (D) is found in Gerupuk 0.88. Based on the value of the Echinoderm community structure on the South Coast of Lombok Island, it shows that diversity is moderate, community uniformity is unstable, and dominance is low. information regarding the distribution and diversity of Echinoderm fauna in various types of habitats around the seagrass as a first step to anticipate the decline in the Echinoderm population in the waters of the South Coast of Lombok Island.